Efektivitas Sidang Keliling (Studi di Pengadilan Agama Wonogiri) - Fauzi, M Latif (Universitas Islam Negeri Raden Intan Lampung, 2017)
This article examines the mobile court policy implemented by the Wonogiri Religious Court. The aim is to find out the effectiveness of the mobile court carried out in expanding access to the justice seekers, especially women. Using the step-by-step theory developed by Rolax, the researcher observes the practices of mobile session conducted by PA Wonogiri around the districts of Puwantoro and Baturetno, about 40 km away from the Wonogiri Religious Courts Office.. The study finds out that, judging from the formal procedural aspect, the mobile courts do have a relatively important role in the expansion of people's access to justice., especially for women, This expansion of access is more meaningful as an effort to provide assistance to the parties so that the time, cost, and energy they spend to attend the session could be more efficient and economical.